2015
DOI: 10.1017/s1431927615000057
|View full text |Cite
|
Sign up to set email alerts
|

The Incorporation of Nanoparticles into Conventional Glass-Ionomer Dental Restorative Cements

Abstract: Conventional glass-ionomer cements (GICs) are popular restorative materials, but their use is limited by their relatively low mechanical strength. This paper reports an attempt to improve these materials by incorporation of 10 wt% of three different types of nanoparticles, aluminum oxide, zirconium oxide, and titanium dioxide, into two commercial GICs (ChemFil® Rock and EQUIA™ Fil). The results indicate that the nanoparticles readily dispersed into the cement matrix by hand mixing and reduced the porosity of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 19 publications
4
39
1
1
Order By: Relevance
“…The mechanical properties of nanofilled composite resins were considered as good as those of universal hybrids (Rastelli et al, 2012). Some studies investigated the use of different nano and microparticles in dental materials, including ZnO, concluding that the use of these particles in small concentrations does not interfere with the mechanical properties of the composite resin (Chen, Yu, Wang, & Li, 2011;Gjorgievska et al, 2015;Sevinç & Hanley, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical properties of nanofilled composite resins were considered as good as those of universal hybrids (Rastelli et al, 2012). Some studies investigated the use of different nano and microparticles in dental materials, including ZnO, concluding that the use of these particles in small concentrations does not interfere with the mechanical properties of the composite resin (Chen, Yu, Wang, & Li, 2011;Gjorgievska et al, 2015;Sevinç & Hanley, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of secondary caries is the accumulation of dental plaque on the surface of dental restorative materials, resulting in the need of replacement of restorations (Burke et al, ; Sakaguchi, ). The use of nano and microparticles to modify dental restorative materials have been grown and researches are focused in development of a restorative material resistant to bacterial accumulation (Gjorgievska et al, ; Corrêa et al, ). The incorporation of metal oxides is one of the approaches that have been used to achieve antibacterial activity into the resin‐based restorative materials (Wang, Shen, & Haapasalo, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified GICs produced by incorporation of different types of nanoparticles have been shown to have fewer air voids and internal microcracks, presumably because they are easier to mix than unmodified cements. In some cases this has resulted in greater compressive strengths [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the specialized literature, a number of studies have reported the successful association of TiO 2 nanotubes with PMMA bone cement [17] and flowable dental composites [16]. Also, the incorporation of TiO 2 nanoparticles in dental resins [19,20] and glass-ionomer cements [21] has resulted in enhanced mechanical properties. However, some studies have suggested that using nanoparticles to enhance the mechanical properties of materials may not be successful due to nanoparticle agglomeration [16,19,22], and, also, so far there are no studies reporting TiO 2 nanostructures' incorporation in ceramic materials.…”
Section: Introductionmentioning
confidence: 99%